Bradycardia secondary to primary hyperparathyroidism. Issue 5 (May 2019) - Liu, Fei; Xin, Zechang; Xia, Yunlong; Yin, Xiaomeng
Clinical doctors rarely associate hyperparathyroidism with significant bradyarrhythmia. We report a rare case of a patient initially misdiagnosed with primary sick sinus syndrome, which was eventually shown to be secondary to primary hyperparathyroidism.